Heat shock protein 70 is involved in polaprezinc driven cell protection against Helicobacter pylori-induced injury - Fansen Meng; Siying Zhu; Meiliang Gong; Hongjin Tao; Weihua Wang; Gangshi Wang (International Journal of Medical Microbiology, 2023)
Polaprezinc (PZ) plays a role in the protection of gastric mucosa and inhibiting Helicobacter pylori (H. pylori) growth in vitro. The objective of this study was to determine the protective effects of PZ on human gastric epithelial cells (GES-1) against H. pylori-induced damage, while also examining heat shock protein 70 (HSP70) as a potential underlying factor in this protection. Our findings revealed that PZ exerted bactericidal effects against H. pylori strains. We also observed that PZ mitigated the H. pylori-induced damage to GES-1 cells by increasing cell viability, reducing LDH release, and decreasing the secretion of pro-inflammatory factors such as MCP-1 and IL-6. Co-culturing PZ with GES-1 cells significantly up-regulated the GES-1 HSP70 expression in both a time and dose-dependent manner. Pre-incubating (for 12 h) or co-culturing (for 24 h) GES-1 cells with PZ reversed the down-regulation of HSP70 in GES-1 cells caused by H. pylori infection. However, when quercetin was used to inhibit the up-regulation of HSP70 in GES-1 cells, the protective effect of PZ on GES-1 cells was significantly reduced. Based on the results of this study, PZ exhibits a protective role on GES-1 cells against H. pylori injury, as well as a direct bactericidal effect on H. pylori. HSP70 is involved in the PZ-driven host cell protection against H. pylori injury. These findings provide insight into alternative strategies for H. pylori treatment.